The Royal Project Packing House quality assurance - Boonyakiat D. (2014)
Temperate fruits and vegetables are grown in the highlands of northern Thailand. Postharvest chain of this produce is collected at the production sites, and transported first to Chiang Mai and then on to Bangkok. There are many postharvest problems which have led to poor quality of produce. The Royal Project Foundation as a charitable organization has developed a permanent agriculture production system in the mountainous areas of northern Thailand. This project has concentrated on developing a suitable way to handle produce from its farmers to customers, putting emphasis on food safety. The project undergoes a food safety system using GMP and HACCP. Many guidelines and personnel training have been investigated to educate the farmers and extension workers. Appropriate temperature management such as cold chain operation for postharvest handling has been introduced to the project. With the help of several organizations, the Royal Project Foundation Packing House has been able to develop appropriate postharvest techniques and a food safety system, which have led to good quality produce.